1988
DOI: 10.1111/j.1768-322x.1988.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Blastema cell proliferation in vitro: Effects of limb amputation on the mitogenic activity of spinal cord extracts

Abstract: Primary cultures of mesenchymal cells of axolotl limb blastemas provide a very sensitive in vitro bioassay for studying nerve dependence of newt regeneration. These cells can be stimulated by crude spinal cord extracts of non-amputated animals in a dose-dependent manner up to 60 micrograms protein/ml of culture medium; at this concentration the mitotic index is increased 4-fold. Spinal cord extracts of axolotls 14 days after forelimb amputation (i.e., late bud stage) are more efficient in stimulating blastema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Experimental work attempting to causally connect protein synthesis in spinal cord and spinal ganglia with the process of limb regeneration has been performed in the past, and has given interesting results [4,9,12,13], which differ from the present investigation in several critical points. One advantage of the study at hand is that it has been performed in vivo.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Experimental work attempting to causally connect protein synthesis in spinal cord and spinal ganglia with the process of limb regeneration has been performed in the past, and has given interesting results [4,9,12,13], which differ from the present investigation in several critical points. One advantage of the study at hand is that it has been performed in vivo.…”
Section: Discussioncontrasting
confidence: 50%
“…In this respect, it was early recognized that the presence of a regeneration blastema on a limb amputation stump prevents retro grade nerve degeneration and exerts other influences on the nerves as well [10,11]. The assumption that these effects might be due to several factors produced by the nervous tissue, the wounded organs and the blastema, has led to a search for such regulative molecules [4,5,9,12,13]. Thereby it was revealed that the central neural elements respond to limb amputation by augmentation in protein synthesis in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to body size, aging and metamorphosis may constrain regenerative capacity by inhibiting the ability of a nerve to produce the vital nerve-derived factor(s). Compared to old individuals, spinal cord extracts from young axolotls are more mitogenic than extracts from old axolotls when added to blastemal cells (in vitro) from a regenerating limb (Boilly & Albert, 1988). This suggests that there is some decrease in the neurotrophic influence of spinal cords across an age gradient in salamanders.…”
Section: (3) Nerve Dependencementioning
confidence: 98%
“…Interestingly, there is evidence that axolotl neurons are affected by age. It was found that spinal cord extracts from older axolotls were diminished in their capacity to stimulate cell proliferation compared to extracts from their younger counterparts, indicating that the nerves are producing less of these neurotrophic factors over time [34]. Moreover, axolotl nerve regeneration is vital for limb regeneration, and as with many vertebrates, the ability to regrow neurons decreases with time.…”
Section: Nerve Function Changes With Agementioning
confidence: 99%